The laughter effect: Enhancing cross-cultural learning and cohesiveness in a virtual environment - Dewey, L A; Abdullah Sidek, 'Atiah (University of Groningen Press, 2024)
This practice report investigates the role of humor in enhancing cross-cultural learning and group cohesion in virtual education settings. Most collaborative international learning training focuses on structuring content, co-teaching, and managing coursework for specific outcomes (Rubin & Guth, 2015). Beyond including time for icebreakers for students to become acclimated with each other, often much of the rest of the experience emphasizes task completion; this serious focus may contribute to discomfort and reduced engagement among diverse students. After witnessing this our first year working together in a collaborative online international learning experience connecting North American students with those from Muslim-majority countries, we explored how modeling and creating opportunities for shared laughter in synchronous group exercises might better promote a relaxed and engaging learning environment. Our findings, derived from qualitative feedback and quantitative surveys, demonstrate that humor enhances group cohesion and cultural exploration. Students reported increased comfort, enjoyment, and willingness to engage and humor-driven activities consistently rated as the most impactful and enjoyable aspects of the course.